Malignant Gliomas as Second Neoplasms in Pediatric Cancer Survivors: Neuropathological Study. (1st April 2018) - Izycka-Swieszewska, Ewa; Bien, Ewa; Stefanowicz, Joanna; Szurowska, Edyta; Szutowicz-Zielinska, Ewa; Koczkowska, Magdalena; Sigorski, Dawid; Kloc, Wojciech; Rogowski, Wojciech; Adamkiewicz-Drozynska, Elzbieta
Abstract : This study presents a unique series of malignant supratentorial gliomas in children previously cured from non-CNS primary cancer. On neuroimaging these tumors were not specific, so the patients were suspected of cerebral recurrence of their primary neoplasm: leukemia in four children and sarcoma in one child. Histologically, the group contained four glioblastomas and one anaplastic astrocytoma. Three patients underwent neurosurgical resection, while the other two underwent stereotactic diagnostic biopsy only. Despite combined oncological treatment, four children died during 20 months, and only one glioblastoma patient continued to live for another twelve years. Microscopically, the neoplasms consisted of small cells with some morphologic features of astrocytic lineage, having scanty or prominent processes. Microvascular proliferation and focal or diffuse necrosis were encountered in four cases. The GFAP reactivity in neoplastic cells was low or nil, together with the expression of Olig2, vimentin, and nestin. In two cases a subpopulation of synaptophysin-positive cells was present. Molecular immunohistochemical profiling revealed the expression of phosphorylated forms of PI3Kp110 and AKT, in parallel to a strong PTEN and p53 positivity. The tumors were of IDH1R132H-wild type and immunoreactive for ATRX, HER3, and EGFR. Secondary malignant gliomas in pediatric cancer survivors pose a diagnostic challenge. The present study shows that these tumors are of IDH wild type, PI3K/AKT-activated, having no PTEN and EGFR mutations. Therefore, the biopsy of brain tumors in such patients is crucial both for accurate diagnosis and material preservation for molecular typing.